Healthcare system access : measurement, inference, and intervention - Serban, Nicoleta, 1975- (Hoboken, NJ : Wiley, 2020)
"This book bridges two areas of research, access modeling and healthcare system engineering, highlighting fundamental approaches on measurement of and inference on healthcare access. It begins with an introduction that provides a broad outline of the motivation and background for the need of understanding access for the healthcare system. The book moves on to characterize healthcare access within a classical multidimensional framework consisting of five dimensions, affordability, accessibility, availability, accommodation and acceptability. It then introduces the concepts of systematic disparities, reviews measures for systematic disparities, and presents a statistical framework for making inference on disparities with application to disparities in access. The book also introduces the concept of health outcomes in the context of prevention and chronic disease management. Final chapters describe the concepts of policy and network interventions and different data sources and structures with various inferential objectives. Health policy in the United States and other countries has embarked on substantive transformation towards improving access to healthcare. The discourse around the topic of healthcare access has brought many innovations in healthcare delivery with enormous opportunities for improvements in the health and wellbeing of the society. However, there is much to be learned about how on-going transformations in healthcare delivery and policy will impact the system in terms of addressing health disparities, improving health outcomes and providing high quality, affordable healthcare for everyone with limited resources"--
A multidimensional framework for measuring access -- Disparities in healthcare access -- Linking access to health outcomes -- Healthcare interventions for improving access -- Data analytics
BIBINDX
Keywords: Health Services Accessibility; Socioeconomic Factors; Healthcare Disparities; Outcome and Process Assessment, Health Care; United States; Electronic books